87.6k views
0 votes
If y(x) = 2x^2 +sqr/5(x-2), complete the following statement:

f(6) =

User Artych
by
5.1k points

1 Answer

6 votes

Answer:

Explanation:

Just plug in 6 as x.


f(6)=2(6)^2+√(5) *(6-2) \\or\\f(6)=2(6)^2+√(5(6-2))

Depending on how the equation is written (I got confused so I gave both answers of what I thought both versions were) this is the answer.


72+4√(5) =2(6)^2+√(5) *(6-2) \\or\\72+2√(5) =2(6)^2+√(5(6-2))

User Sergio Martins
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.